'A social justice logic': how digital commerce enables value co-creation at the bottom of the pyramid. Issue 9 (13th June 2021) - Utami, Hesty Nurul; Alamanos, Eleftherios; Kuznesof, Sharron
ABSTRACT: The paper conceptualises digital technology as a source of innovation in value co-creation (VCC) at the bottom of pyramid (BOP) markets through fieldwork focused on vegetable supply chains in Indonesia. An inductive analysis based uponin-depth, semi-structured interviews with multiple business actors identified VCC in an emerging e-commerce channel where digital technologies enabled engagement and interaction amongst channel members. The results suggest that market scripting based upon an inclusive, collaborative and empowerment ideology, which can lead to sustainable development and income redistribution from consumers to producers, was explicitly embedded in their VCC agenda. Fair-trade practices supported customer-driven innovations. For consumers, digital technologies created online 'consumption communities' where information and educational interactions supported online food purchases and innovation in the supply chain 'pull' strategies. The paper concludes that the logic underpinning this new transformative business approach of digitally enabled VCC in local BOP markets is akin to a 'social justice logic'.